Cash Waqf: A Literature Study Using the Systematic Literature Review (SLR) and Bibliography Methods - Oktavia, Nursyam; Nurwahidin; Hannase, Mulawarman; Nafis, Muhammad Cholil; Fatwa, Nur; Muttaqin, Mohammad Izdiyan (PT FORMOSA CENDEKIA GLOBAL, 2024)
To analyze cash waqf as a preference for waqf by utilizing systematic literature review (SLR) and bibliometric analysis to identify and synthesize relevant articles from published national and international journals. Using an integrated analysis of Systematic Literature Review (SLR) and Bibliometric methods on 1,109 journal articles indexed in the Scopus database. The PRISMA protocol yielded 60 research articles eligible for review and synthesis related to cash waqf, with saturation achieved through 10 articles. Cash waqf can be an effective tool in driving economic growth. The publication and citation performance over the past ten years of observation is relatively high, with an average citation